The strangeness in writting - Souyris Oportot, Lorena (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The present article tries to put in tension the discourse of the institutionalization legitimized knowledge under canonical designations in language. In this sense, through a strangeness in writing and from the work of Maurice Blanchot, the normative violence inscribed in the rhetoric circumscribed in the forms of language will be put on trial. All this in order to propose, starting from the fragmentary writing, a "surplus value" of the narrating voice that manifests as excess in writing. The idea is, therefore, to make possible the staging of an "inter-dit" (between-saying) as an area that opens to an aestheticisation of the contribution that not only constitutes a "poetic" of the critical discourse, but also offers an unfinished understanding that deconstructs the closed explanation.